Assessing post-hazard damage costs to a community's residential buildings exposed to tropical cyclones. Issue 4 (20th November 2020) - Wang, Cao; Zhang, Hao; Ellingwood, Bruce R.; Guo, Yanlin; Mahmoud, Hussam; Li, Quanwang
Abstract: Assessment of the potential for damage to community's residential buildings exposed to extreme natural hazards is essential for measuring and optimising resilience enhancement strategies for communities. This paper develops a probability-based method to estimate the potential for damage and losses to a community's residential building portfolio due to tropical cyclones (TC) by aggregating the performance of individual buildings quantitatively. The proposed approach reflects the fact that the total building damage of a community depends on the specific TC scenario and the correlation in performance of different individual buildings due to correlations in intensity in the wind field and common construction practices. The estimated damage potential, conditioned on the maximum TC wind speed, is determined from the TC fragilities. The mean value and variance of the cyclone-induced damage losses are estimated using an approximate closed-form approach. The applicability of the proposed method is demonstrated for a small coastal community in North Australia and the sensitivity of the estimated TC damage losses to the key characteristics of the TC wind field and building portfolio is investigated. It is found that correlations in building performance due to common TC demand and construction practices have a significant impact on losses to the community.